Proses Pembuktian Penguasaan Narkotika yang Disimpan di Dalam Helm - Sony Wijanarko (Fakultas Hukum Universitas Surabaya, 2020)
This article aims to examine the truth of the possession of shabu-shabu Narcotics found in NS's helmets which allegedly mastered the Narcotics so it must be proven through the process of proof according to applicable formal law. Research in this paper uses a normative juridical research method, namely research that is examined using primary legal material consisting of legislation, jurisprudence. In addition to being studied using primary legal materials, this study was also conducted using secondary legal materials consisting of doctrines, principles, and scienti